An Analytical Study on Hybrid Working and its effect on the Future Working of the Personnel’s in Mumbai (International Journal of Food and Nutritional Sciences, 2022)
Every industry trend in the world today is talking about the hybrid workplace. as digitalization becomes more commonplace in all facets of the global village. To ease into the hybrid workplace, every workplace must maximize and overcome obstacles and innovations. The work from home likewise turns out to be more pertinent during the pandemic. The research was carried out at a corporate IT company in Mumbai. The purpose of this research paper was to comprehend the effects of both the hybrid and work-from-home models, as well as their various drawbacks and advantages and the employees' preference for the future work model. The study was conducted using primary data and a simple random sampling method with a sample size of 120 employers. to investigate the advantages and disadvantages of the hybrid and work-from-home models, as well as the employees' preferences regarding the future work model. This data collection made use of simple frequency analysis, the independent sample T-test, the Chi square test, and one-way ANOVA as statistical tools. According to the study's findings, employees are pleased with their decision to adopt a hybrid work model in the future. Employees are free to work where and when they feel most at ease.